Determination of certain sol-gel growth parameters of nickel oxide films. Issue 2 (March 2015) - Turgut, G.; Sonmez, E.; Duman, S.
Abstract: In present work, NiO thin films were fabricated by sol-gel spin coating technique depending on precursor concentration, annealing temperature and solvent type. Crystallographic, morphological and optical features of films were inquired by XRD, AFM and UV/VIS measurements. The XRD studies pointed that films had nickel oxide cubic structure with (200) preferential orientation and the crystallinity of films depended on deposition conditions. The AFM pictures showed the films were composed of well-formed nano particles. From AFM analysis, it was also found that deposited films had quite smooth surfaces. The optical measurements indicated that the transmittance and optical band gap values continuously decreased with the increasing precursor molarity, however they initially increased with the annealing temperature up to 550 °C and then dropped off with more increasing annealing temperature. For 2-methoxyethanol, methanol and water solvents, the highest optical transmittance and optical band gap values were found for methanol solvent. The findings in our study suggest that the characteristic properties of NiO films strongly depend on the deposition conditions of sol-gel spin coating. NiO films with good structural, morphological and optical properties can be also used in various technological applications.